Accuracy of root-end resection using a digital guide in endodontic surgery: An in vitro study - Li Peng; Jing Zhao; Zu-Hua Wang; Yu-Chun Sun; Yu-Hong Liang (Elsevier, 2021)
Background/Purpose: It is difficult to achieve accurate root-end resection clinically. This in vitro study was conducted to evaluate the operation accuracy of a digital endodontic surgical guide. Materials and methods: 56 extracted maxillary anterior teeth were prepared for endodontic surgical models. The models were randomly divided into 4 groups equally according to the guide (with guide/no guide) and the operator (experienced/inexperienced). Endodontic microsurgeries were performed on models in each group. The deviations in length and angle of the root-end resection were measured based on the optical scanning data of the pre- and postoperative teeth. The general linear model was performed to analyze the effect of a guide on root-end resection deviation. Results: Using a guide, the mean length deviation for experienced/inexperienced operators reduced from 0.99 mm (95% CI [confidence interval, CI], 0.66-1.33 mm)/1.18 mm (95% CI, 0.50-1.86 mm) to 0.31 mm (95% CI, 0.20-0.42 mm)/0.31 mm (95% CI, 0.24-0.37 mm). The mean angle deviation for experienced/inexperienced operators reduced from 16.74° (95% CI, 10.61-22.86°)/15.06° (95% CI, 9.19-20.94°) to 5.04° (95% CI, 3.31-6.77°)/6.79° (95% CI, 4.91-8.67°). The difference was significant between procedures performed with and without a guide (P < 0.01). Conclusion: Application of the digital guide in vitro endodontic surgery could improve the accuracy of root-end resection.